2007
DOI: 10.1111/j.1365-3040.2007.01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Root growth dynamics of Nicotiana attenuata seedlings are affected by simulated herbivore attack

Abstract: Many studies demonstrate resource-based trade-offs between growth and defence on a large timescale. Yet, the short-term dynamics of this growth reaction are still completely unclear, making it difficult to explain growthdefence trade-offs mechanistically. In this study, imagebased non-destructive methods were used to quantify root growth reactions happening within hours following simulated herbivore attack. The induction of wound reactions in Nicotiana attenuata in the seedling stage led to transiently decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 55 publications
8
54
0
1
Order By: Relevance
“…This suggests that many metabolic processes are downregulated belowground when defense mechanisms are induced in leaves. In accordance with this, a rapid and transient reduction of root growth after shoot herbivore attack occurs in N. attenuata [87]. It remains to be investigated if this reduced investment into growth is a part of the strategy of plants to ''turn down its spatial expansion and strengthen its function as a safe retreat'' [87] or if it helps to liberate additional resources to boost leaf defenses.…”
Section: Roots As Environmental Sensors and Root-shoot Signal Emittersmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that many metabolic processes are downregulated belowground when defense mechanisms are induced in leaves. In accordance with this, a rapid and transient reduction of root growth after shoot herbivore attack occurs in N. attenuata [87]. It remains to be investigated if this reduced investment into growth is a part of the strategy of plants to ''turn down its spatial expansion and strengthen its function as a safe retreat'' [87] or if it helps to liberate additional resources to boost leaf defenses.…”
Section: Roots As Environmental Sensors and Root-shoot Signal Emittersmentioning
confidence: 99%
“…Known shoot-root signals such as auxins [89] and other phloem-borne molecules including proteins [90] and small RNAs [91] are candidates for such investigations. Furthermore, it has been suggested that the reduction of root growth after leaf wounding could be mediated by a hydraulic signal [87]. Interestingly, sucrose is not only a simple assimilate that is moved to roots for tolerance purposes upon insect attack but also by a potential shoot-root signal [92].…”
Section: Roots As Environmental Sensors and Root-shoot Signal Emittersmentioning
confidence: 99%
“…Primarily for this reason, assessment of REGRs from two-dimensional (2D) observation of growing roots (single-point perspective) has largely been conducted on restrictive 2D surfaces such as glass plates (Erickson & Sax, 1956;Basu et al, 2007) or Petri dishes (Hummel et al, 2007;Mullen et al, 1998;Nagel et al, 2006). These data are recognized as being informative despite ongoing * ** r e t f A e r o f e B Fig.…”
Section: Researchmentioning
confidence: 99%
“…The increased flux of C to the roots in response to herbivory would be expected to increase the rate of root growth, but in young seedlings of N. attenuata, for example, sometimes just the opposite occurs (Hummel et al, 2007). Unlike the FAC-elicited C flux, this rapid inhibition of root growth requires an intact JA-signaling cascade (G.M.…”
Section: Herbivore-induced Changes In Assimilation and Partitioning Omentioning
confidence: 99%